Myths, Misperceptions, and Policy Learning: Comparing Healthcare in the United States and Canada. Issue 4 (2018) - Marchildon, Gregory P.; Cafaro, Capri S.; Brown, Adalsteinn
Abstract : The U.S. and Canadian health care systems are more similar than is commonly believed. This article debunks some of the powerful myths about these health care systems and opens up the discussion for greater policy learning from both sides of the border. Cross-border comparisons can yield a number of lessons from common policy challenges such as cost control, physician organization and payment, and the organization of health coverage and services for Native Americans and Indigenous Canadians.